Clinical nutrition in gastrointestinal disease - Buchman, Alan (SLACK, 2006)
Provides a practical guide that examines and explains the necessary elements and principles of nutrition. With more than 100 images and 180 tables, this unique and comprehensive text provides essential information to optimally and successfully manage patients. Some topics covered include: Nutritional assessment; Nutrition in critical care; Nutritional support; Management of intestinal failure; and, Obesity. Some gastrointestinal diseases covered include: Inflammatory bowel disease; Irritable bowel syndrome; Colon cancer; Pancreatititis; Heptic failure; and, Celiac sprue.